2015
DOI: 10.1371/journal.pone.0119718
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A8 Identifies a Subpopulation of Transiently Quiescent c-Kit Positive Luminal Progenitor Cells of the Ductal Mammary Epithelium

Abstract: We have previously shown that Annexin A8 (ANXA8) is strongly associated with the basal-like subgroup of breast cancers, including BRCA1-associated breast cancers, and poor prognosis; while in the mouse mammary gland AnxA8 mRNA is expressed in low-proliferative isolated pubertal mouse mammary ductal epithelium and after enforced involution, but not in isolated highly proliferative terminal end buds (TEB) or during pregnancy. To better understand ANXA8’s association with this breast cancer subgroup we establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Indeed, ANXA2 plays a key role in the establishment of epithelial polarity and lumenogenesis by regulating actin cytoskeleton dynamics at the apical surface of the plasma membrane and recruiting to this compartment the Cdc42 Rho-GTPase [3, 22]. Similarly, ANXA8, known to be expressed in a subset of mammary progenitor cells and upregulated during mammary gland remodeling [19, 31], is involved in the formation of endosomes [15], which are implicated in the establishment and maintenance of epithelial cell polarity [16]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, ANXA2 plays a key role in the establishment of epithelial polarity and lumenogenesis by regulating actin cytoskeleton dynamics at the apical surface of the plasma membrane and recruiting to this compartment the Cdc42 Rho-GTPase [3, 22]. Similarly, ANXA8, known to be expressed in a subset of mammary progenitor cells and upregulated during mammary gland remodeling [19, 31], is involved in the formation of endosomes [15], which are implicated in the establishment and maintenance of epithelial cell polarity [16]. …”
Section: Discussionmentioning
confidence: 99%
“…ANXA2 not only is known to be involved in the regulation of membrane dynamics and actin remodeling [17], but also plays a key role in the establishment of epithelial cell polarity and lumen formation [3, 22], two fundamental processes required for normal mammary epithelial morphogenesis. Conversely, apart from evidence of ANXA8 expression in a subpopulation of mammary progenitor cells [19] and its modulation during mouse mammary gland involution [31], less clear is the morphogenetic function of ANXA8.…”
Section: Introductionmentioning
confidence: 99%
“…Early research on APL identified that over-expressed ANXA8 plays a significant role in the signal transduction pathway in the APL cells [12][13][14][15]. It has been reported that ANXA8 expression is apparently upregulated in breast cancer, with a great relevance of tumor stages, grades and positive lymph nodes [17][18][19]. Of note, ANXA8 is crucial in the maintenance of the late endosomal/lysosomal compartment physiological functions in cancer cells [16] and is able to interact with phosphatidylinositides and actin-associated membrane domains [25] which are closely related to cell migration, cytokinesis, vesicle transport and cellular immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, ANXA8 has also been linked to the formation of endosomes and epidermal growth factor receptor (EGFR) turnover in Hela cells [16]. Other reports demonstrated that the expression of ANXA8 is significantly increased in breast cancer [17][18][19], pancreatic cancer [20][21][22], ovarian cancer [23] and cholangiocarcinoma [24]. Thus, ANXA8 is expected to be a new biomarker and molecular therapeutic target for the diagnosis, treatments and prognosis of multiple diseases, especially malignant tumors.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…Altered expression of annexin A4 is related to endometrial receptivity during the implantation window in infertile patients with endometriosis (Jiang, Li, Xing, Wang, & Feng, ). A previous study has shown that one member of annexin family, ANXA8 , has an impact on the proliferation, quiescence and colony formation in mouse mammary epithelial cells (Iglesias et al, ). The low expression of ANXA8 leads to sprouting angiogenesis, migration and adhesion deficiency (Heitzig et al, ).…”
Section: Introductionmentioning
confidence: 99%